Examining the Crisis Leadership of Public-Private Partnership in Ecological Based Tourism of Bromo Tengger Semeru - I Gede Eko Putra Sri Sentanu; Zakky Zamrudi; Ardik Praharjo; Bambang Santoso Haryono; Gibriel Badjie (Universitas Muhammadiyah Malang, 2024)
This study is aimed to evaluate the role of crisis leadership within the public-private partnership of tourism collaborative governance. This study employs a cross-sectional study involving 304 respondents from various stakeholder from Bromo-Tengger-Semeru National park (BTSNP). The study employs the SEM-PLS data analysis to evaluate the measurement model and structural model. The results of the study indicates that the important role of Public-Private partnership on collaborative governance is only indicated by several dimension, especially those of Governance, Mutuality, and Administration. However, the interaction moderation indicates that crisis leadership is only able to enhance the Mutuality and Norm and Trust. The further discussion related to the finding is elaborated within the papers. The originality of this paper is by presenting a picture of ecological tourism management in Indonesia through the lens of public-private-partnership.